Cohesive Zone Model Estimation of the Tensile Behaviour of Adhesive Joints - R. L. Fernandes; R. D. S. G Campilho (Techniques and Innovation in Engineering Research Vol. 3, 2022)
Cohesive Zone Models (CZM) are commonly used in numerical techniques for the damage simulation of bonded joints based on fracture mechanics. Mainly three methods can be used to derive the CZM laws: the property identification technique, the inverse method and the direct method. This study looked at the tensile fracture toughness (GIC) and CZM laws of bonded joints for two different adhesives. The DCB (Double-Cantilever Beam) test has been used. The experimental effort involved using the J-integral approach to characterise the tensile fracture properties of two structural adhesives. To measure the tensile relative displacement (dn) of the adhesive layer at the fracture tip, a computerised image correlation approach was used. To analyse the accuracy of triangular, trapezoidal, and linear-exponential CZM laws in predicting the experimental behaviour of the DCB tests, FE simulations were performed. This paper provides information about the applicability of these CZM rules to each type of adhesive, allowing for the subsequent strength prediction of bonded joints.